ANALISA PERBANDINGAN HASIL PENGUJIAN LABORATORIUM DAN SIMULASI PADA BALOK BETON BERTULANG - Sudarno P Tampubolon (PADURAKSA: Jurnal Teknik Sipil Universitas Warmadewa, 2021)
A reinforcement concrete beam behavior is substantial to design structure. Some failures can found in the beam because the beam reinforcement structure does not install like procedure design, this problem made failure for the structure. Knowing the behavior of the beam structure resulting from the load is necessary, as it can help to predict the strength of the structural beam and comfort of the structure being worked on. To find out and predict the strength and comfort of the structure reinforced concrete beam as a result of the load received is the experimental test and simulation. The simulation VecTor2 was used to predict the shear force, crack, and displacement of the reinforced concrete beam when applied to the displacement load. This simulation considered the effect of the bond stress-slip effects of behavior reinforced concrete. Bonds stress-slip (0.139) gives a substantial influence on the strength and hysteretic response of the reinforced concrete beam. That is why this study considers the effect of the bond stress-slip on reinforced concrete. The results of the experiment test and simulations performed, the ratio of load capacity ranges from 1.00-1.095, and the crack pattern forms an angle of 45. All the results of simulation VecTor2 using the bond stress-slip effect would be compared with the result of the experimental test to see the behavior and accuracy of the simulation test.